Analisis kesulitan membaca pemahaman pada peserta didik kelas VD SD Djama’atul Ichwan Surakarta - Riska Putri Wahyu Lestari; Rukayah Rukayah; Siti Kamsiyati (Didaktika Dwija Indria, 2021)
This study aims to describe the difficulties of students in the VD class of Djama'atul Ichwan Elementary School in the 2020/2021 academic year in reading comprehension. This study used a qualitative descriptive method where the data collection techniques used observation, interviews, and written tests to 6 respondents. Based on the results of data analysis and discussion, this study found difficulties in reading comprehension in students. Difficulty reading comprehension in students is shown through indicators of students' abilities in answering questions about reading content, finding main ideas, making reading conclusions, determining mandates, and the ability to retell the content of the reading. Data analysis in the discussion provides broad and in-depth information about the difficulties of different students regarding reading comprehension.